The Analysis Of Mathematical Connection Ability In Two-Variabel Linear Equation System Based On Self Regulated Learning Of Students In VIII Grade Of Mts Negeri 1 Kota Makassar - Nur Fadillah Musfira; Nurdin Arsyad; Rusli Rusli; Hastuty Musa; Abdul Rahman (PT ARRUS Intelektual Indonesia, 2025)
This study aims to analyze students' mathematical connection skills based on self-regulated learning in solving math problems in the Two-Variable Linear Equation System material. This research is qualitative research with a descriptive approach. The subjects in this study were class VIII MTs Negeri 1 Makassar City consists of two students for each level of high, medium, and low self-regulated learning. The research instrument used consisted of the main instrument, namely the researchers, and also the supporting instruments, namely a self-regulated learning questionnaire, a mathematical connection ability test, and an interview guide. The results showed that: (1) subjects who had high self-regulated learning met three indicators of mathematical connection, namely being able to recognize and use ideas in mathematics and understand the interrelationships of these ideas, and being able to recognize and apply mathematics in contexts in other fields of study. And able to relate mathematics in daily life. (2) subjects who have moderate self-regulated learning only meet two indicators of mathematical connections, namely being able to recognize and use ideas in mathematics and understand the interrelationships of these ideas, and being able to recognize and apply mathematics in the context of daily life. (3) Subjects who have low self-regulated learning, namely subjects R1 and R2 were unable to fulfill the three indicators of mathematical connection. Subject R1 was only able to fulfill one indicator of mathematical connection, while subject R2 did not fulfill any indicator of mathematical connection.